Spinal anaesthesia for emergency cesarean section in neurofibromatosis for an antepartum haemorrhage: a case report - Kour, Gunmeet; Sharma, Shivani; Sharma, Deeksha; Singh, Gurbir (International Journal of Research in Medical Sciences, 2024)
Neurofibromatosis 1 (NF1) is an autosomal dominant disease and is usually diagnosed during childhood. Neurofibromatosis are group of genetic disorders that cause tumors to form, which can develop anywhere in the nervous system including brain, spinal cord and nerves. It poses a great challenge to the anaesthesiologist as it may have difficult airway, fibrosis in lungs and neuromas in spinal cord. Due to the involvement of CNS, regional anaesthesia in type 2 neurofibromatosis without careful preoperative examination can be extremely dangerous. Regional anaesthesia on the other hand could be useful in type 1 neurofibromatosis because CNS involvement is rare. This was a case report of management in a 24-year-old pregnant female with undiagnosed neurofibromatosis for an emergency cesarean section for antepartum haemorrhage and IUD under spinal anaesthesia. Although general anaesthesia is the safer option in neurofibromatosis patients, spinal anaesthesia can be a safe procedure in neurofibromatosis patients but special precautions should be taken to avoid neurological injury and uneventful anaesthesia.